2012
DOI: 10.1245/s10434-012-2824-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival after Definitive (Chemo)Radiotherapy in Esophageal Cancer Patients: A Population-Based Study in the North-East Netherlands

Abstract: Long-term results and the local control rate in SCC patients were better after definitive (chemo)radiotherapy compared with in AC patients. SCC was an independent prognostic factor for survival. Definitive chemoradiotherapy leads to improved local control rate and DFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…A recent meta-analysis including 6 major studies with a total of 929 patients reported 2-year overall survival rates between 35 and 58% using definitive chemo-radiotherapy [22]. Another trial investigating 287 patients showed 2-year survival rates of 29% for patients suffering from esophageal squamous cell carcinoma and 19% for those with adenocarcinoma [23]. …”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis including 6 major studies with a total of 929 patients reported 2-year overall survival rates between 35 and 58% using definitive chemo-radiotherapy [22]. Another trial investigating 287 patients showed 2-year survival rates of 29% for patients suffering from esophageal squamous cell carcinoma and 19% for those with adenocarcinoma [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Squamous cell carcinoma is the most common type of EC worldwide, with a higher incidence in developing countries and a 5‐year survival rate less than 15% [Liu et al, ]. Current therapies for EC include surgery, radiation, and chemotherapy, in which radiotherapy is mainly used for patients with no tolerance to surgery or having un‐resectable tumors [Smit et al, ]. However, the radio‐resistance of EC remains an obstacle for the effective radiotherapy of EC [Huang et al, ].…”
mentioning
confidence: 99%
“…Phase III randomized trials comparing CCRT with radiation alone [12][13][14][15][16] have made CCRT the standard treatment for patients with inoperable esophageal cancer. However, there are only a few studies comparing the definitive CCRT with surgery alone for esophageal cancer, most of which are prospective Phases I and II clinical trials and retrospective studies, [20][21][22] and only a few of which are randomized clinical trials.…”
Section: Surgery Vs Definitive Crt For Esophageal Cancermentioning
confidence: 99%